PERCEPTION VERSUS PUNISHMENT IN CYBERCRIME. - GRAVES, JAMES T.; ACQUISTI, ALESSANDRO; ANDERSON, ROSS (Journal of Criminal Law & Criminology)
The article provides an overview on punishment in cybercrime. Topics discussed include factors that affect the maximum sentences under the Computer Fraud and Abuse Act of 1986; factors that determine the recommended sentences under the federal sentencing guidelines promulgated by the U.S. Sentencing Commission; and enactment of Sentencing Reform Act of 1984 for governing sentencing in the country.